2012
DOI: 10.1371/journal.pone.0050979
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Injury Preventive Warm-Up Programs on Knee Strength Ratio in Young Male Professional Soccer Players

Abstract: PurposeWe aimed to investigate the effect of FIFA 11+ (11+) and HarmoKnee injury preventive warm-up programs on conventional strength ratio (CSR), dynamic control ratio (DCR) and fast/slow speed ratio (FSR) in young male professional soccer players. These ratios are related to the risk of injury to the knee in soccer players.MethodsThirty-six players were divided into 3 groups; FIFA 11+, HarmoKnee and control (n = 12 per group). These exercises were performed 3 times per week for 2 months (24 sessions). The CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 35 publications
5
126
3
8
Order By: Relevance
“…In studies investigating the correlation between core exercises and sporting performance, sportspeople with core training were not identified to have positive development in sporting performance (Stanton et al 2004, Tse et al 2005, Nesser et al 2008). Contrary to this, there are research results reporting that adding core training to football training significantly developed strength and power (Brito et al 2010, Daneshjoo et al 2012. The causes of these differences in study results may be that studies were applied in different branches like swimming, rowing, and football and that branch-specific techniques may affect power production during movement.…”
Section: Discussionmentioning
confidence: 93%
“…In studies investigating the correlation between core exercises and sporting performance, sportspeople with core training were not identified to have positive development in sporting performance (Stanton et al 2004, Tse et al 2005, Nesser et al 2008). Contrary to this, there are research results reporting that adding core training to football training significantly developed strength and power (Brito et al 2010, Daneshjoo et al 2012. The causes of these differences in study results may be that studies were applied in different branches like swimming, rowing, and football and that branch-specific techniques may affect power production during movement.…”
Section: Discussionmentioning
confidence: 93%
“…The way this ratio was calculated in the present study provides important information about knee flexor/extensor imbalance along the entire joint range of motion in female futsal players, and might allow for the identification of possible injury risks during this range of motion. The HQ ratio is frequently used as an index to evaluate the stabilizing efficiency of the knee joint muscles [9][10][11] . In this study, HQ ratios varied throughout the joint range of motion, with lower values at 30° to 45° of knee flexion, and higher values at 65° to 80°.…”
Section: Discussionmentioning
confidence: 99%
“…The hamstrings/quadriceps peak torque ratio (HQ ratio) is an index used to evaluate the stabilizing efficiency of the knee joint muscles 9,10 . Specifically, it measures the ability of the hamstrings to neutralize tibial anterior translational forces produced by the knee extensors, providing dynamic joint stability during knee extension [9][10][11] . It is well established that the HQ physiological peak torque ratio is 60% on average, representing the level of muscular balance.…”
Section: Introductionmentioning
confidence: 99%
“…In order to simulate the situation where hamstring strain occurs, athletes were instructed to forward incline the trunk when sprinting. Conversely, Daneshjoo et al 27 observed no effect of two typically recommended specific injury prevention programmes (FIFA 11 + and Harmo Knee) to enhance hamstring strength in professional football players. More recently, Naclerio et al 24 reported that four weeks (12 sessions) of an injury prevention programme comprising three sets of eight repetitions of the Nordic curl, forward lunges on a Bosu ® , balance trainer and eccentric single-leg dead lifts was effective in improving the maximal isometric force at both closed (80°) and open (35°) knee angles.…”
Section: Unstable-core and Sport Specific Exercisesmentioning
confidence: 97%
“…In addition, to the active lengthening observed during sprints or kicking, the hamstring acts as knee stabilisers counteracting and balancing the actions of the quadriceps during sportspecific activities, such as landing, deceleration or change of direction. Therefore, specific drills involving, repeated sprints, jumps, hops combined with unstable coreexercises, namely one-leg squat or lunges unstable surfaces have been proposed as effective methods for preventing hamstring injuries 24,27,28 . Verral et al 28 reported a significant reduction of hamstring injuries in Australian football players after a four-year high-intensity intervaltraining programme combined with passive isometric hamstring stretching.…”
Section: Unstable-core and Sport Specific Exercisesmentioning
confidence: 99%